A Pre Review On The Interaction Component In Formulating Sustainable Supply Chain Management - Wan Mahmood, Wan Hasrulnizzam; Mohamed, Norhafiza; Muhamad, Mohd Razali; Yusup, Mohd Zaki (Publications International Lahore, Pakistan, 2014)
The purpose of this paper is to explore the basic interaction components in formulating sustainable supply chain management. Sustainable Supply Chain is one of the advance technology approaches that compete with high productivity and less cost. In order, to achieve best performance on sustainability, the process of Supply Chain Management must accomplish and through with the management of industry. Process of Supply Chain Management includes five elements, which are; planning, procurement, production, delivery and response level. All the processes have their own interaction on manufacturing. The interaction framework in this paper can be used by manufacturers and researchers to gain more understanding on process of sustainable supply chain management.